2015
DOI: 10.1136/bmjopen-2015-008018
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of the impact and acceptability of a polypill for prevention of cardiovascular disease

Abstract: ImportanceThe Use of a Multidrug Pill In Reducing cardiovascular Events (UMPIRE) trial has shown improved adherence with the use of a polypill strategy when compared with usual medications for cardiovascular disease (CVD) prevention. To advance from efficacy to impact, we need a better understanding of why and how such a strategy might be deployed in complex health systems.ObjectiveTo understand, from the perspective of UMPIRE trial participants and professionals, how and why a polypill strategy improves adher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…While a polypill was acceptable to most patients of the UMPIRE trial, some felt that FDC therapy was less tailored to individual patient needs. 49 A recent investigation of the views of cardiovascular patients and providers who participated in polypill trials reported similar advantages and concerns to those identified in our study, 50 suggesting that polypill perspectives translate to other regions and healthcare settings.…”
Section: Discussionsupporting
confidence: 79%
“…While a polypill was acceptable to most patients of the UMPIRE trial, some felt that FDC therapy was less tailored to individual patient needs. 49 A recent investigation of the views of cardiovascular patients and providers who participated in polypill trials reported similar advantages and concerns to those identified in our study, 50 suggesting that polypill perspectives translate to other regions and healthcare settings.…”
Section: Discussionsupporting
confidence: 79%
“…Those results would suggest the importance of FDC in high-risk patients in terms of preventing CVD 1–3. Those were in accordance with our results and could be explained by the simplicity of a single polypill and the strong motivation in established or high risk patients to stay healthy 22. Therefore, in patients with established CV diseases or at high risk, a clear benefit of FDC was observed as indicated in cases of clustering risk factors such as dyslipidaemia, hypertension, and diabetes 3 23.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the costs of treatment with the polypill for primary and secondary CVD prevention, several studies have shown that the cost benefits of polypill use were significantly lower than the use of component drugs given separately. In addition, the patient and doctor acceptance of the polypill were significantly higher compared with the component drugs given separately . .…”
Section: Clinical Evidence Demonstrating the Importance Of Crf Modifimentioning
confidence: 90%
“…In addition, no problems have been found between the component drugs of the polypill regarding bioavailability and pharmacokinetic interactions . With respect to the effectiveness and costs of the polypill, these have been shown to be highly acceptable by patients and doctors alike . In fact, the polypill has been called “a best bargain” for the primary and secondary prevention of CVD and strokes.…”
Section: Possible Composition Of the Polypillmentioning
confidence: 99%
See 1 more Smart Citation